2014
DOI: 10.1134/s1063773714040069
|View full text |Cite
|
Sign up to set email alerts
|

Special point on the mass-radius diagram of hybrid stars

Abstract: An analytical study that explains the existence of a very small region on the mass-radius

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 14 publications
4
36
0
Order By: Relevance
“…As the transition density rises the radius of a 1.4 M star decreases at first, but then increases again. This is related to the previously noted fact [30] that when one fixes the speed of sound of quark matter and increases the bag constant (which increases p trans /ε trans and also varies ∆ ε/ε trans in a correlated way) the resultant family of mass-radius curves all pass through the same small region in the M-R plane: the M(R) curves "rotate" counter-clockwise around this hub (see Fig. 2 of Ref.…”
Section: Radius Of a 14 M Starmentioning
confidence: 58%
See 1 more Smart Citation
“…As the transition density rises the radius of a 1.4 M star decreases at first, but then increases again. This is related to the previously noted fact [30] that when one fixes the speed of sound of quark matter and increases the bag constant (which increases p trans /ε trans and also varies ∆ ε/ε trans in a correlated way) the resultant family of mass-radius curves all pass through the same small region in the M-R plane: the M(R) curves "rotate" counter-clockwise around this hub (see Fig. 2 of Ref.…”
Section: Radius Of a 14 M Starmentioning
confidence: 58%
“…2 of Ref. [30]). In our case we are varying p trans /ε trans at fixed ∆ ε/ε trans , so the hub itself also moves.…”
Section: Radius Of a 14 M Starmentioning
confidence: 88%
“…As the transition density rises the radius of a 1.4 M star decreases at first, but then increases again. This is related to the previously noted fact [27] that when one fixes the speed of sound of quark matter and increases the bag constant (which increases p trans /ε trans and also varies ∆ε/ε trans in a correlated way) the resultant family of mass-radius curves all pass through the same small region in the M-R plane: the M(R) curves "rotate" counterclockwise around this hub (see Fig. 2 of Ref.…”
Section: Typical Radius Of Hybrid Starsmentioning
confidence: 60%
“…2 of Ref. [27]). In our case we are varying p trans /ε trans at fixed ∆ε/ε trans , so the hub itself also moves.…”
Section: Typical Radius Of Hybrid Starsmentioning
confidence: 88%
“…[29]). A recent study [30] has found, that EoS from the class of CSS models share the property that all M-R curves, regardless of the hybrid star onset density, must cross a small region in the M-R diagram, the SP. We would like to extend this study to a wider range of EoS with additional microscopic features, such as vector repulsion, and investigate the possibility that the existence of a SP is a universal property of hybrid neutron star models.…”
Section: Introductionmentioning
confidence: 99%